Character Education Concepts and Values in The Teaching of Gratitude (A Critical Analysis of Major Qur’anic Exegesis Texts) - Akif Khilmiyah; Wahid Setiawan (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
This paper aimed to explore and find the concept and content of character values of being grateful. This research was library research using qualitative data types. The primary sources were Tafsr al-Qurān al-'Aẓῑm, Tafsr al-Fakhri ar-Rāzi, Tafsr al-Maraghi, at-Tafsῑr al-Munῑr, Tafsr al-Karῑm ar-Raḥmān fā Tafsῑr Kalām, and Tafsir al-Azhar. At the same time, secondary sources were books or journals related to the concept of gratitude and the value of character education. Data from sources were collected using documentation, then analyzed using subjective thematic interpretation methods and objective hermeneutics. The results showed that the concept of character education in the teaching of gratitude in QS. Ibrahim (14): 7 is both targῑb (motivation) and tarhῑb (threat). This concept will make humans remain in the circle of goodness, who is always patient and grateful to Allah SWT. There are nine values of character education in the teaching of gratitude: trustworthiness, qanā'ah, creativity, hard work, trustworthiness, optimism, caring for others, tawaduk, and istiqamah. These values will be attached to someone who makes gratitude a habit that can be both a motivation and a threat (targῑb wa tarhῑb). These nine character values will have implications for increasing devotion to Allah SWT and increasing compassion for fellow creatures.